2011
DOI: 10.3748/wjg.v17.i25.3027
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, genotypes and factors associated with HCV infection among prisoners in Northeastern Brazil

Abstract: Most of the HCV transmissions result from parenteral exposure. However, there is evidence to suggest a role for sex and household contact with an infected subject in virus transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
2
17
1
1
Order By: Relevance
“…Otherwise, this prevalence is not consistent with previous studies conducted among inmates in Brazil, such as in Sergipe (3.1%), São Paulo (9.0%) and Campo Grande, MS, (4.8%) and higher than in Espírito Santo (1.0%) [1417]. Although this prevalence is greater than the prevalence in the general population, the low prevalence found may be due to current low prevalence of HCV exposure in the Midwest region.…”
Section: Discussioncontrasting
confidence: 82%
“…Otherwise, this prevalence is not consistent with previous studies conducted among inmates in Brazil, such as in Sergipe (3.1%), São Paulo (9.0%) and Campo Grande, MS, (4.8%) and higher than in Espírito Santo (1.0%) [1417]. Although this prevalence is greater than the prevalence in the general population, the low prevalence found may be due to current low prevalence of HCV exposure in the Midwest region.…”
Section: Discussioncontrasting
confidence: 82%
“…Another important infection, especially in schistosomiasis endemic areas, is viral hepatitis, particularly that caused by hepatitis B virus (HBV) and hepatitis C virus (HCV) 6 . Viral hepatitis is a serious public health problem, not only in Brazil but also in many other countries worldwide 7,8 . Despite the controversies in the literature about the prevalence of schistosomiasis and viral hepatitis coinfection, some reports have indicated that the presence of both infections accelerates and aggravates the process of fibrosis in the liver and can lead to the development of cirrhosis and hepatocellular carcinoma 3 .…”
mentioning
confidence: 99%
“…In Aracaju, Santos et al (2011) found that 3.1% (13/422) of participants Gabe and Lara (2008) found 9.21% (7/76) anti-HCV positive. These studies revealed higher rates of anti-HCV positive in prison populations than in the nonprison population, which was confirmed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…In Brazil, information about hepatitis C has become more accessible following the publication of several studies (Paltanim, Reiche, 2002;Zarife et al, 2006;Strazza et al, 2007;Fagundes et al, 2008;Gabe, Lara, 2008;Coelho et al, 2009; Ferrao et al, 2009;Mousquer, Castro, 2009;Silva et al, 2010;Oliveira-Filho et al, 2010;Santos et al, 2011). Fagundes et al (2008) found that 2.2% (10/457) of adults in Criciúma (Santa Catarina) were anti-HCV positive and that 1.53% (7/457) were HCV RNA-positive, but the study did not identify the HCV genotype (16).…”
Section: Discussionmentioning
confidence: 99%